The Characterology of Stepan Baley: Some Psychological and Philosophical Comments - Honcharenko, Olha (Filozofia Nauki, 2022)
This article aims at identifying the relevance of character research, conducted by Stepan Baley, a representative of the Ukrainian branch of the Lviv-Warsaw School. To achieve this, the author first analyzes the key points of Baley’s characterology, and then demonstrates its potential from the perspective of Twardowski’s philosophical tradition and within the ethical debate on the empirical approach to character. The author concludes that it is impossible, according to Baley, to obtain accurate and complete knowledge of character, as well as it is impossible to educate a person in a certain way.